Uji Teratogen Ekstrak Akar Jarong (Stachytarpheta jamaicensis (L.) Vahl.) terhadap Sistem Reproduksi Mencit (Mus musculus L.) Betina - Agustinus Renyoet; Raynard C. Sanito (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
This study aim to determine the teratogens effect of jarong (Stachytarpheta jamaicensis (L.) Vahl) roots extract on the reproductive system of mice (Mus musculus L.) female Swiss Webster organogenesis during pregnancy.The method used in this study is the method of extraction and examination of vaginal smears.. The experiment was conducted in August-December 2010, at the Laboratory of Zoology, Department of Biology Cenderawasih University, Jayapura. The Experiment was carried out by dividing the 20 female mice into 4 groups. One group is a control group and with no treatmen and the other 3 groups were tretaed with oral treatments.. The results obtained in the qualitative descriptive analysis. It could be concluded that ethanol extract of jarong (Stachytarpheta jamaicensis (L.) Vahl) roots cause of accidental poisoning in mice, embryotoxic and causes the effects of teratogens. Key words: Jarong (Stachytarpheta jamaicensis (L.) Vahl), teratogens effect, mice (Mus musculus L.).